Bearing Steels: Into the 21st Century 1998
DOI: 10.1520/stp12122s
|View full text |Cite
|
Sign up to set email alerts
|

What Happens to the Fatigue Limit of Bearing Steel Without Nonmetallic Inclusions? : Fatigue Strength of Electron Beam Remelted Super Clean Bearing Steel

Abstract: This paper has two objectives. The first is to propose a new inclusion rating method based on statistics of extreme. The new inclusion rating method is applied to the evaluation of inclusions contained in two super clean bearing steels with a total oxygen level of 5ppm and 8ppm. The second objective is to investigate the critical lower bound of inclusion size which influences the fatigue limit. For this purpose, a special steel with extremely low inclusion content, the electron beam remelted sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 9 publications
0
11
0
Order By: Relevance
“…Few results are given in the specialized literature on this topic 1 . According to our own observations and those of Murakami et al ., 8 fatigue crack initiation in the gigacycle regime seems to occur essentially inside the sample and not at the surface as is observed for shorter lives.…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…Few results are given in the specialized literature on this topic 1 . According to our own observations and those of Murakami et al ., 8 fatigue crack initiation in the gigacycle regime seems to occur essentially inside the sample and not at the surface as is observed for shorter lives.…”
Section: Discussionmentioning
confidence: 48%
“…Figure 11 presents an example of the N18 alloy. In this respect, the Murakami model 8 is a good approach to predict fatigue strength as depending on the inclusion size in the gigacycle regime 9 …”
Section: Discussionmentioning
confidence: 99%
“…Murakami et al 33 . conducted rotary bending fatigue tests on a bearing steel produced by a special melting method.…”
Section: S–n Curvesmentioning
confidence: 99%
“…This effect of inclusions on the fatigue limit is in fact generally accepted [49], [50]. Murakami et al observed that the fatigue limit of bearing steel tended to increase as the size of inclusions decreased over the years due to better steelmaking practices [51]. For 13%Cr-4%Ni steels, silicon and aluminum complex oxides are found in different proportion and sizes.…”
Section: 5mentioning
confidence: 90%